The relationship between real GDP, CO2 emissions, and energy use in the GCC countries: A time series approach - Cosimo Magazzino (Cogent Economics & Finance, 2016)
This paper examines the relationship among real GDP, CO2 emissions, and energy use in the six Gulf Cooperation Council (GCC) countries. Using annual data for the years 1960-2013, stationarity, structural breaks, and cointegration tests have been conducted. The empirical evidence strongly supports the presence of unit roots. Cointegration tests reveal the existence of a clear long-run relationship only for Oman. Granger causality analysis shows that for three GCC countries (Kuwait, Oman, and Qatar) the predominance of the "growth hypothesis" emerges, since energy use drives the real GDP. Moreover, only for Saudi Arabia a clear long-run relation has not been discovered. Finally, the results of the variance decompositions and impulse response functions broadly confirm our previous empirical findings. Our results significantly reject the assumption that energy is neutral for growth. Notwithstanding, since the causality results are different for the six GCC countries, unified energy policies would not be the good recipe for the whole area.
Keywords: B22; C32; N55; Q43; 330; economic growth; CO2 emissions; energy use; GCC countries; time series